Corticosteroids and Severe Community-Acquired Pneumonia: A Systematic Review - Iwuji, Kelechi Adannaya; Thwe, Hla; Akinsanya, Olabisi Basirat; Firew, Eden; Atiba, Oluwatobi; Onumajuru, Cindy; Irfan, Huma; Qaiser, Saria; Ogbu, Uzoamaka Amara; Abdelhadi, Nahid Ahmed; Chijioke, Chidinma; Gopal, Shwetha; et al. (Journal of Advances in Medicine and Medical Research, 2025)
Background: In recent years, there has been growing interest in the potential role of corticosteroids as adjunctive therapy in severe. Community-acquired pneumonia (CAP) cases. It is a significant global health burden, contributing substantially to infectious disease-related morbidity and mortality. Severe management presents challenges, often requiring intensive supportive measures and aggressive antimicrobial therapy. Corticosteroids have garnered interest as adjunctive therapy due to their anti-inflammatory effects, hypothesised to modulate the exaggerated host immune response in severe pneumonia. Aim: In this systematic review, we aim to address the gap in knowledge by conducting a rigorous evaluation of the outcomes associated with corticosteroid therapy as an adjunctive treatment in severe CAP. Methods: This systematic review followed PRISMA 2020 guidelines. Eligible studies focused on severe CAP patients receiving corticosteroid therapy in randomised controlled trials (RCTs). Information sources included PubMed, Embase, and the Cochrane Library, with manual searches of journals and conferences. Data were extracted, synthesised, and analysed to evaluate corticosteroid efficacy and safety. Results: Of 1016 studies screened, six RCTs were included, totalling 2772 participants. Interventions included various corticosteroids administered adjunctively for severe CAP. Studies assessed outcomes such as mortality, duration of mechanical ventilation, length of hospital stay, and complications. Significant findings included reduced mortality with hydrocortisone adjunctive therapy, shorter length of hospital stay with oral dexamethasone, and expedited clinical stability with prednisone. However, no significant mortality reduction was observed with prolonged low-dose methylprednisolone. Corticosteroids were generally well-tolerated, albeit with an increased risk of hyperglycemia. Conclusion: Corticosteroid therapy as adjunctive treatment shows promise in improving outcomes for severe CAP patients, including reduced mortality and shorter hospital stays. However, conflicting findings and varying treatment regimens underscore the need for further research to optimise corticosteroid use in this context. Standardised protocols, long-term follow-up assessments, and subgroup analyses are recommended to enhance understanding and guide clinical practice effectively. In sum, the use of corticosteroids as adjunctive therapy in severe CAP shows promise in reducing mortality rates and improving clinical outcomes.